Validity Evidence of the Persevering Hope Scale: Internal Structure and Flourishing Relationship in Adolescents - Lesmana, Teguh; Rani Lidiawati, Krishervina; Emilio Nathaniel, Darryn (Universitas Islam Indonesia, 2025)
In recent years, the validity and relevance of psychological measurement tools have become a major research concern, particularly when used in different cultural contexts. One psychological construct that demonstrates the urgency of accurate measurement is persevering hope—a form of hope that persists in conditions of uncertainty and adversity. This study aimed to adapt the Persevering Hope Scale into the Indonesian language and examine its validity evidence based on internal structure and its relationship with flourishing among adolescents in the Jabodetabek area. This research employed a quantitative method with a cross-sectional design. A total of 924 adolescents were selected using convenience sampling. Data analysis was conducted using Confirmatory Factor Analysis (CFA) with AMOS to assess the validity and reliability of the instrument, as well as Spearman correlation analysis to examine the relationship between persevering hope and flourishing. The CFA results indicated that only 4 out of the original 15 items demonstrated a good model fit for the Indonesian population (CFI = 1.000; RMSEA = 0.000). Additionally, the scale showed good reliability, with a Composite Reliability (CR) of 0.833 and an Average Variance Extracted (AVE) of 0.56. Since the data did not meet the assumption of multivariate normality, Bollen-Stine Bootstrap testing was conducted, yielding a p-value of 0.441 (> 0.05), indicating an acceptable model. Spearman correlation analysis revealed a significant positive relationship between persevering hope and flourishing (r = 0.510, p < 0.01). These findings suggest that higher levels of persevering hope are associated with greater levels of flourishing among adolescents. The implications of this study highlight the importance of developing interventions to enhance persevering hope as a means to support adolescent mental well-being.